Coronal Balance vs. Sagittal Profile in Adolescent Idiopathic Scoliosis, Are They Correlated? - Ma, Qichao; Wang, Lin; Zhao, Lihua; Wang, Yicheng; Chen, Mengjie; Wang, Sun; Lv, Zhibao; Luo, Yi (Frontiers in Pediatrics, 2020)
Background: Clinical evaluation of the postural balance in adolescent idiopathic scoliosis has been measured by coronal and sagittal parameters. The relationship between them has not been fully studied. Objective: This study aimed to evaluate the correlation between coronal and sagittal parameters for idiopathic scoliosis. Methods: 103 patients of Adolescent Idiopathic Scoliosis (AIS) were recruited. Radiographs were evaluated for the following spine and pelvic measurements. Coronal parameters including thoracic Cobb angle (TC), lumbar Cobb angle (LC), global coronal balance (GCB), apical translation of the major curve (AT), coronal pelvic tilt (CPT). Sagittal parameters including thoracic kyphosis (TK), lumbar lordosis (LL), sagittal vertical axis (SVA), pelvic incidence (PI), pelvic tilt (PT) and sacral slope (SS). A canonical correlation analysis was performed between all the coronal parameters and sagittal parameters. Results: 103 patients were recruited (male 15, female 88; aged 12.5 ±1.5 years). Compared with the published age-matched normal population, TK, PI, LL and SS were not statistically different from the normal group; however, PT was significantly increased (P=0.003). Canonical correlation analysis showed significant associations between coronal parameters and sagittal parameters, F (20, 313) = 2.44, p =0.001. SVA was not correlated with any coronal parameter. Conclusions: Children with AIS showed signs of increased pelvic tilt. In the study, TC, LC, GCB, AT, CPT, TK, LL, SVA, PI, PT and SS contributed to the postural balance. In AIS, coronal balance is correlated to sagittal balance.